Achieving excellence through creativity: Gülen’s vision of character education - Shehu, Fatmir Mehdi (2011)
The school curricula vision of the most developed countries, beginning with the industrial development period until today, has aimed at promoting career based knowledge while ethics and values have been peripheral to student development. Hence, there is a need to impart morals and virtues to students. Gülen Educational Movement, inspired by the thoughts and works of Fethullah Gülen, has emerged in order to integrate the career based knowledge of education with that of character based knowledge. This paper seeks to examine: firstly, the distinguished creativity mindset of Gülen in initiating an excellent system of education whose vision is to serve humanity by providing them moral orientation and guidance that makes them orderly and law-biding citizens. Secondly, Gülen's vision of character education that has provided new insights into how scholar-scientists, people of religion, members of the arts, and state officials make it possible to coexist and serve society. Thirdly, the way how Gülen and the Movement operate and sustain their schools and universities. This paper will provide significant findings and resolutions that will benefit individuals, communities and humanity at large.